Research and development of integrated life cycle risk management and control platform for large petroleum storage depot - Xiping ZHU (You-qi chuyun)
In order to ensure energy security and realize the "dual carbon" strategy, it is urgent to strengthen the risk management and control of large oil and gas storage facilities while vigorously improving the storage capacity of oil and gas. In response to the problems of large petroleum storage depots concerning database construction, risk prediction and early warning, and emergency decision-making support, the key technologies adopted during the platform operation were optimized with reference to the general implementation requirements specified in the Aboveground Petroleum Storage Depot Integrity Management Specification (GB/T 42097—2022). Specifically, the core architecture of the integrated risk management and control platform for large petroleum storage depots and a life cycle database were established, a quantitative risk assessment method based on the domino effect was formed, and an emergency decision-making support sub-system was developed. Besides, an emergency rescue route optimization model for petroleum storage depots was built by improving the Dijkstra algorithm, and a fire analysis algorithm and an emergency drone platform were developed. Moreover, an integrated life cycle risk management and control platform was established based on SINOPEC Zhoushan petroleum storage depot, which effectively enhanced the decision-making level on management and safety of petroleum storage depot from multiple aspects, such as full life cycle data management, risk prediction and early warning, and emergency management. Generally, the research results could provide technical support for the safe operation of petroleum storage depots.